Studi Komparatif: Implementasi Kebijakan Luar Negeri Indonesia Dan Kuwait Terkait Pemberian Humanitarian Aid Terhadap Polemik Palestina – Israel - Alia, Nazwa; Zebua, Kerenhapukh Valentina; Simbolon, Sherly Desinta; M, Natasya Ulkhaira Adhian; Haliawan, Prity Oktora; Noer, Arvenia; Yuningsih, Neneng Yani (Jurnal Kajian Pemerintah: Journal of Government, Social and Politics, 2024)
The Palestinian conflict with Israel has been going on for centuries, beginning in the mid-1800s/ Tensions rose with Jewish migration to Palestine and the 1917 Balfour Declaration in favor of establishing a "national home for the Jewish people" in Palestine, exacerbating land and identity conflicts. Israel's annexation in 1980 also added to political tensions and territorial struggles. The conflict has become an international issue since the end of the World War, leading to a protracted humanitarian crisis that has drawn global attention, including from Indonesia and Kuwait. The governments of Indonesia and Kuwait oppose violence in Palestine and are committed to providing humanitarian assistance through foreign policy. This paper explains how the comparison of the implementation of the results of diplomacy and foreign policy related to humanitarian assistance to the Palestinian-Israeli polemic carried out by Indonesia and Kuwait is connected through Holsti's public policy theory, namely foreign policy as a cluster of orientations, foreign policy as a set of commitments to and a plan for actions, foreign policy as a form of behavior to see the extent to which the effectiveness of assistance from these countries to Palestine is researched through the literature study research method.